Basic Rules Related to Obligation – A Contemporary Applied Usūlī Study - Jaber, Saleh (Jordan Journal of Islamic Studies, 2025)
Objectives: This study aims to clarify the true nature of the usūlī (principles of Islamic jurisprudence) rules related to obligations, to identify and enumerate the most important of these rules, and to highlight their impact on contemporary reality. Methods: The researcher adopted a descriptive approach, which is evident in describing contemporary issues and presenting the general meanings of the rules. A partial inductive method was also used by tracing scholarly opinions, meanings, and contemporary cases. Results: The study reached several conclusions, the most prominent of which is the clarification that usūlī rules related to obligations are general rulings that guide jurists in applying what the Lawgiver has commanded in a binding manner. It was found that the rules related to obligation are not limited to the five rules discussed in the study. The impact of these rules was clearly demonstrated in a number of contemporary applications. Conclusions: The study highlights the theoretical aspect within contemporary practical applications through several cases, including: crowding during the continuity (muwālāt) of ṭawāf (circumambulation), induced abortion before the soul is breathed into the fetus, astronomical calculations, the conflict between the obligation of spending in the cause of Allah and performing the pilgrimage to the Sacred House as a non-obligatory act, and a mujahid killing himself out of fear of disclosing Muslims’ secrets.